2017
DOI: 10.1039/c7fd00161d
|View full text |Cite
|
Sign up to set email alerts
|

Introductory lecture: atmospheric chemistry in the Anthropocene

Abstract: The term “Anthropocene” was coined by Professor Paul Crutzen in 2000 to describe an unprecedented era in which anthropogenic activities are impacting planet Earth on a global scale. Greatly increased emissions into the atmosphere, reflecting the advent of the Industrial Revolution, have caused significant changes in both the lower and upper atmosphere. Atmospheric reactions of the anthropogenic emissions and of those with biogenic compounds have significant impacts on human health, visibility, climate and weat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 580 publications
0
13
0
2
Order By: Relevance
“…Nitrous acid is generated in the gas phase, with indications that it results from the decomposition of the -NO 2 containing CI. This acid absorbs strongly in the actinic region that reaches Earth's surface, and, through its photolysis, it is a major source of the OH radical that drives the chemistry of the atmosphere (17,65). While the NPM−O 3 reaction is not expected to be a significant source of HONO relative to other known outdoor and indoor sources on a global basis (66,67), it may play a role locally where NPM is used, and its production in this reaction is certainly of mechanistic interest.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrous acid is generated in the gas phase, with indications that it results from the decomposition of the -NO 2 containing CI. This acid absorbs strongly in the actinic region that reaches Earth's surface, and, through its photolysis, it is a major source of the OH radical that drives the chemistry of the atmosphere (17,65). While the NPM−O 3 reaction is not expected to be a significant source of HONO relative to other known outdoor and indoor sources on a global basis (66,67), it may play a role locally where NPM is used, and its production in this reaction is certainly of mechanistic interest.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, experiments in thin water films containing nitrate, chlorine, and bromine salts have shown that the photolysis of NO 3 – occurs much faster at interfaces than in the bulk, ,, with J values ranging between 1.2 × 10 –3 and 3 × 10 –6 s –1 , depending on the features of the interface. ,,, A potential explanation for this enhancement is associated with the solvation of nitrate anion. In bulk water, nitrate is surrounded by a solvent cage that facilitates both the recombination of the NO 2 and OH radicals produced by reaction and their deactivation by collision with solvent molecules, thus decreasing the photolysis quantum yield. ,,, MD simulations have shown that when halide anions (especially bromide) are present, nitrate ions are dragged closer to the interface so that the water solvent cage surrounding them is reduced, , arguably making the escape of NO 2 to the gas phase easier. ,, Nevertheless, despite the large amount of work done on nitrate photochemistry, open issues remain that are not yet completely understood. For instance, it was recently shown that an important part of nitric acid remains undissociated at the air–water interface, , and the relevance of the corresponding photochemistry is still undetermined.…”
Section: Photochemistry Of Oh Precursorsmentioning
confidence: 99%
“…On one hand, field observations have shown that the photolysis of HNO3 adsorbed on the forest canopy surface is an important source of HONO. 82 On the other hand, experiments in thin water films containing nitrate, chlorine, and bromine salts have shown that the photolysis of NO " % occurs much faster at interfaces than in the bulk, 63,81,[90][91][92][93][94] with J values ranging between 1.2 × 10 −3 s −1 and 3 × 10 −6 s −1 depending on the features of the interface. 63,83,95,96 A potential explanation for this enhancement is associated with the solvation of nitrate anion.…”
Section: Reactive Nitrogen Species (Rns)mentioning
confidence: 99%
“…The setup utilized a flow-through reactor to provide the reactive uptake coefficient of ozone on catechol films [61] under variable humidity conditions, and elucidated the formation of quinones as well as biphenyl and terphenyl rings [61]. Present and future laboratory, chamber, and field studies to examine the product mixtures resulting from these mechanisms are being inspired [152][153][154][155][156][157][158][159][160][161][162][163] by this work, to gather information for inclusion in the next generation of computational models to predict the effects of aerosols on climate.…”
Section: Outcomes Learned From Recent Interfacial Studiesmentioning
confidence: 99%